Viability of encapsulated Lactobacillus sp. Mar 8 - EVI TRIANA; EKO YULIANTO; NOVIK NURHIDAYAT (Society for Indonesian Biodiversity, 2006)
Lactobacillus sp. Mar 8 had advantages as probiotic digestive system cholesterol lowering Lactobacillus. Applying in industry, particular processing technique is necessary for gaining product that ready for marketing and consuming. Spray drying is common technique using in various food processing. High processing temperature, 100-200oC, for 3-10 second become the barrier because cells were under extreme temperature stress. Therefore, encapsulate was needed to protect the cells from those extreme conditions. Viability and survival rate of encapsulated Lactobacillus sp. Mar 8 have been investigated. The result showed that Lactobacillus sp. Mar 8 that was encapsulated by 10% skim milk has higher viability than those by 5% skim milk, namely 72.37% and 51.69% respectively. Survival rate of encapsulated Lactobacillus cells will come to zero in 41.28 years. Therefore, encapsulated Lactobacillus sp. Mar 8 may use as probiotic agent. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Lactobacillus sp. Mar 8, viability, spray drying, encapsulation, survival rate.